2016
DOI: 10.1177/1358863x16668588
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dabigatran versus warfarin in patients with acute venous thromboembolism in the presence of thrombophilia: Findings from RE-COVER®, RE-COVER™ II, and RE-MEDY™

Abstract: It is unclear whether thrombophilia causes resistance to anticoagulant therapy. Post hoc analyses of data from RE-COVER, RE-COVER II, and RE-MEDY were performed to compare dabigatran etexilate with warfarin for the treatment and prevention of venous thromboembolism (VTE) in patients with thrombophilia or antiphospholipid antibody syndrome (APS). There were no significant differences in symptomatic VTE/VTE-related deaths between dabigatran etexilate and warfarin in patients with or without thrombophilia. All bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 19 publications
2
89
0
1
Order By: Relevance
“…72 An analysis from the RE-COVER/RE-COVER II and RE-MEDY trials showed similar safety and efficacy of dabigatran in patients with thrombophilia and previous venous thromboembolic events, in whom APS represented the second most common inherited disorders, accounting for 20% of all patients. 79 These results need to be confirmed in realworld studies. A randomized trial investigating the efficacy and safety of apixaban in APS patients is currently ongoing; 80 this study will include patients with both venous and arterial thrombosis.…”
Section: Secondary Antiphospholipid Syndromementioning
confidence: 95%
“…72 An analysis from the RE-COVER/RE-COVER II and RE-MEDY trials showed similar safety and efficacy of dabigatran in patients with thrombophilia and previous venous thromboembolic events, in whom APS represented the second most common inherited disorders, accounting for 20% of all patients. 79 These results need to be confirmed in realworld studies. A randomized trial investigating the efficacy and safety of apixaban in APS patients is currently ongoing; 80 this study will include patients with both venous and arterial thrombosis.…”
Section: Secondary Antiphospholipid Syndromementioning
confidence: 95%
“…Currently for patients with hereditary thrombophilia, DOACs are not usually the primary anticoagulant recommended under these conditions (9)(10)(11)59). In the RE-MEDY trial, small subgroup analysis, dabigatran seemed noninferior to warfarin in thrombophilia patients (protein C or S deficiency, antithrombin deficiency, antiphospholipid antibodies, FV Leiden or prothrombin variant heterozygous mutation) (62). Rivaroxaban was assessed as noninferior to warfarin in phospholipid antibody syndrome (APS) in a phase III trial (63); however, the most severe APS patients did not benefit from rivaroxaban in comparison with warfarin (64).…”
Section: Oral Anticoagulation and Thrombophiliamentioning
confidence: 99%
“…One of the NOACs could be a more convenient alternative for this patient once she stops breastfeeding, and there are emerging data from case series 54 and subgroup analyses from larger trials 22 that NOACs are similarly effective in patients with antiphospholipid syndrome. However, until a current randomized trial has demonstrated efficacy results, 55 NOACs should not be the first line of treatment because failures have been reported.…”
Section: Case 2: Antiphospholipid Syndromementioning
confidence: 99%
“…22 It has been speculated that deficiency of antithrombin may be associated with heparin resistance. In a retrospective review of 70 patients with congenital antithrombin deficiency, we found 8 patients in whom there was some clinical deterioration on treatment with unfractionated heparin.…”
mentioning
confidence: 99%